Islamization of Science Naquib Al-Attas's Perspective - Katni Katni; Fista Nurjanah; Wawan Yulianto; Nur Aisyah; Fais Farkhani; Elfy Kameiliya Rahmah (CV. Bimbingan Belajar Assyfa, 2025)
The advancement of Islamic science, which once dominated world civilization, was the culmination of the integration of the values ​​of the spirit of Islamic teachings with science and technology, although the journey faced significant challenges. According to al-Attas, the greatest challenge facing Muslims in the Islamization of Islamic Science was the knowledge disseminated throughout the Islamic world by Western civilization. The Islamization of knowledge means the Islamization or purification of Western scientific products that have been developed and used as a reference in the discourse on the development of the Islamic education system in order to obtain a science that is